Formação de nomes aumentativos: estudos da produtividade de alguns sufixos portugueses - Rosa, Maria Carlota Amaral Paixão (1982)
Study of the augmented names of the Portuguese in a lexicalist view. Its objective is to analyze the productivity of ten suffixes listed as augmentative in descriptive-normative works. An overview of the degree of augmentative is presented, with the intention of specifying both concepts. The analysis of the suffixes follows the discussion. The results of the analysis reveal a clear distinction between productive and nonproductive augmentary suffixes, thus providing additional evidence for previous proposals for separation between word formation rules and redundancy rules. Non-focused phenomena are also described in the traditional treatment of augmentative names in Portuguese.